2003
DOI: 10.1111/j.1547-5069.2003.00119.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors Related to Nausea, Vomiting, and Fatigue in Early Pregnancy

Abstract: Only a limited number of psychosocial factors were associated with nausea and vomiting and fatigue in early pregnancy. Depression was related to physical symptoms, but unclear was whether depression preceded or resulted from the symptoms. Many women experienced symptoms, and better understanding of causality is needed to ameliorate the effects on women's well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
74
1
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 40 publications
8
74
1
7
Order By: Relevance
“…Depression is also common during gestation, a ecting approximately 10-15% of women [3]. ere have been several studies examining the relationship between NVP and depression [4][5][6][7][8]; however, the authors were not able to establish if depression preceded or resulted from the symptoms of NVP. In a preliminary study by our group, depression and treatment with antidepressants prior to and during early pregnancy were not associated with the occurrence of NVP; however, the severity of neither NVP nor depression were examined at that time [9].…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Depression is also common during gestation, a ecting approximately 10-15% of women [3]. ere have been several studies examining the relationship between NVP and depression [4][5][6][7][8]; however, the authors were not able to establish if depression preceded or resulted from the symptoms of NVP. In a preliminary study by our group, depression and treatment with antidepressants prior to and during early pregnancy were not associated with the occurrence of NVP; however, the severity of neither NVP nor depression were examined at that time [9].…”
mentioning
confidence: 68%
“…ey used the 20-item Center for Epidemiologic Studies Depression Scale (CES-D) to measure depressive symptoms and a checklist to examine the frequency of occurrence of NVP (occasional, frequent or absent) to establish NVP. ey concluded that pregnant women without NVP had signi cantly lower CES-D scores than did women with frequent NVP, suggesting that depressive symptoms were positively correlated with NVP [5].…”
Section: Discussionmentioning
confidence: 99%
“…The development of Nausea and Vomiting in Pregnancy (NVP) is rife, affecting approximately 80% of pregnant females, where only 1% of these might progress to develop a severe form of NVP known as hyperemesis gravidarum [1][2][3] . NVP is commonly seen between the 5 th and the 18 th weeks of gestation, and affect the overall well-being of patients 4 .…”
Section: Introductionmentioning
confidence: 99%
“…These complaints may have an onset in the first trimester and remain until the end of pregnancy and be observed in 75% of all pregnancies (3). It is reported that the severity of complaints might vary from one to another and even from one pregnancy to the other of the same person while they were seen at any time of the day despite its highest occurrence in the morning (4).…”
Section: Introductionmentioning
confidence: 99%